Analisis Kontrastif Ejaan Bahasa Indonesia Dengan Bahasa Melayu Tulisan Jawi Dan Implementasinya Sebagai Materi Ajar - Mumoo, Miss Farihah, Prof. Dr. Markhamah, M.Hum (2016)
This study aims to. (1) Describe the similarities and differences phonemes between Indonesian and Malay jawi writing. (2) Describe differences in the application letter in Indonesian words writing and Malay Jawi writing language. (3) Describe differences in writing form the Indonesian language and Malay Jawi Writing. (4) Describe the implementation it as teaching material spelling comparison Indonesian language and Malay Pattani language. This research is qualitative research the method of this research is descriptive and kind of this research is library research. The data of research are phoneme and vocabulary in Indonesian and Malay Jawi language. The technique of collecting data is reading the source to refer method and documentation. The technique of analyze data is analysis contrastive method is used to find difficulties which is faced the students to learn grammatical so that can be found suitable method to solve it. The result of this research is revealed that are twenty one of Indonesian consonant. Consonant that is different between two languages are /ث - s (th)/, /ح-h (ḥ)/, /ﺥ-kh/, /ﺫ-z (dh)/, /ﺵ- sy (sha)/, /ﺹ- s (ṣ)/, /ﺽ- d (ḍ)/, /ﻁ- t (ṭ)/, /ﻅ- z (ẓ)/, /ﻉ- a, k (')/, /ﻍ- gh/, /ڠ- ng/, /ڽ- ny/, and/ﻻ/. Others are same. There are five vowel in Indonesian language are, a, e, i, o, u and there are three vowels of Malay Jawi such as ﺍﻭ andﻱ. From the both phoneme and vowel in Indonesian and Malay Jawi have a big similarities, the different of Indonesian and Malay Jawi's vowels only ﻭ and ﻱ each of them have two equivalent phoneme and vowel in Indonesian language, ﻭ = o, u danﻱ = e, i. The different implementation of vowel in Indonesian and Malay Jawi writing, the different just some words in Malay Jawi that writing is not symbol with vowel but spelling with that vowel. Repeating word in Indonesian and Malay Jawi language in this research is four kin of repeating word, main repeating word, appearance repeating word, affixing repeating word and sound changes repeating word. The writing main repeating word and appearance repeating word in Indonesian and Malay jawi are so different. Because writing of these repeating word in Indonesian spelled by hyphen (-), while in Malay Jawi language using symbol of number two in Arabic. (۲) as spelling of repeating word. And others are same. The result appropriate becoming a teaching material in grade two Ibtida'iyah. Key word: contrastive analysis, Indonesian and Malay Jawi Spelling, Implementation